The carpet people ebook - Pratchett, Terry (2020)
The  New York Times  bestselling author of the Discworld series delivers “fantasy with comedic flair” in his debut novel and first children’s book ( VOYA ).   In the beginning, there was nothing but endless flatness. Then came the Carpet . . .    That’s the old story everyone knows and loves. But now the Carpet is home to many different tribes and peoples, and there’s a new story in the making. The story of Fray, sweeping a trail of destruction across the Carpet. The story of power-hungry mouls—and of two brothers who set out on an adventure to end all adventures when their village is flattened.    It’s a story that will come to a terrible end—if someone doesn’t do something about it. If everyone doesn’t do something about it . . .    First published in 1971, this hilarious and wise novel marked the debut of the phenomenal Sir Terry Pratchett. Years later, Sir Terry revised the work, and this special collectable edition includes the updated text, his original color and black-and-white illustrations, and an exclusive story—a forerunner to  The Carpet People  created by the seventeen-year-old nascent writer who would become one of the world’s most beloved storytellers.   “Only a writer with a masterstroke of imagination could place an entire empire of goodies and baddies within the fronds of a carpet.”— Daily Mail “The perfect starting place for young readers; seasoned Pratchett fans will just revel in his wit, his subversion of tropes and his sense of humanity . . . Small in scale but large in pleasure.”— Kirkus Reviews “Brilliantly funny dialogue, high peaks of imagination.”— The Times